Glyphosate and AMPA-Induced Apoptosis and Epigenetic Alterations in HepG2 Cells: Upregulation of P53-BAX-CASP Pathways - Mehtiyev, Tugrul; Guler, Zeynep Rana; Aktan, Elif; Ozden, Sibel (Pergamon-Elsevier Science Ltd, 2025)
Glyphosate and its metabolite aminomethylphosphonic acid (AMPA) are environmental contaminants with potential toxic effects. This study aimed to investigate apoptosis and epigenetic alterations induced by glyphosate and AMPA in HepG2 cells. The IC50 values for glyphosate and AMPA were 6.19 mM and 8.13 mM, respectively, following 24 h exposure; mechanistic assays were conducted at sub-cytotoxic concentrations (50-500 mu M). Annexin V/PI flow cytometry revealed that AMPA significantly increased early apoptosis (up to 116 %, p < 0.001), while glyphosate elevated late apoptosis (up to 145 %, p < 0.001). Gene expression analysis showed significant upregulation of p53 (>= 1.49-fold), BAX (>= 1.82-fold), CASP3 (>= 1.37-fold), and CASP9 (>= 1.83-fold), with no significant change in BCL2. Epigenetic analysis indicated that both glyphosate and AMPA increased global DNA methylation, with fold changes ranging from 1.43 to 1.62-fold at concentrations of 100-250 mu M (p < 0.05). DNA methyltransferase genes DNMT1 (>= 2.44-fold), DNMT3A (>= 1.65-fold), and DNMT3B (>= 1.65-fold) were upregulated. Additionally, histone modification profiling showed elevated levels of H3K27me3, H3K9me3, and H3K9ac (p < 0.05), alongside increased expression of G9a (>= 1.64-fold), EZH2 (>= 2.14-fold), SETD1B (>= 2.15-fold), HAT1 (>= 2.40-fold), and SIRT1 (>= 2.57-fold), and downregulation of SUV39H1 (>= 0.27-fold). These findings reveal the molecular mechanisms of glyphosate and AMPA toxicity, linking apoptosis to epigenetic alterations and enhancing understanding of their risks.
Guler, Zeynep Rana/0000-0003-0817-4315; Mehtiyev, Tugrul/0000-0002-8701-7985
Keywords: Glyphosate; AMPA; Apoptosis; DNA Methylation; Histone Modification; HepG2 Cells; DNA Methylation; HepG2 Cells